Evaluation of the Eating Attitude of Handball Players - Samar, Ezgi; Togay Unaldi, Gamze (Progress in Nutrition, 2021)
Study Objectives: This study aimed to evaluate the eating attitudes of handball players according to some variables. Methods: One hundred twenty volunteer handball players participated in the study. The questionnaire consisted of the information questionnaire that determined the demographic characteristics and the eating attitude test EAT-26, which was adapted to Turkish by Devran (2014). After the scales were prepared on google-form, the research was announced on social media, and participation was provided voluntarily. When the data used in the study were analyzed with the Kolmogorov-Smirnov test, the Mann-Whitney U, and Kruskal-Wallis tests, which were nonparametric. Results: In the study, normal eating attitudes and behaviors were observed in 83.3% of the athletes, and abnormal eating attitudes and behaviors were observed in 16.7%. When the eating attitude scores of the athletes were compared according to the variables of gender, nutrition program implementation, dietitian support, and body weight perception, a statistically significant difference was observed, and no difference was observed in terms of age, educational status, sports age, weekly training time (p <0.05). Moreover, it was found that the difference in the sub-dimensions was significant according to the gender and body weight perception variable, the eating attitude scores of females were higher than males was due to the bulimic behavior sub-dimension, and according to the bodyweight perception, it was found that the athletes who stated themselves as weak in the oral control behavior dimension (p <0.05). Conclusion: When the eating attitude scores of the athletes according to gender, nutritional program application status, dietician support variables, and body weight perception were compared, significance was found (p <0.05). It was known that eating disorders had very negative effects on athlete’s health and performance. Therefore, unhealthy exercise and diet programs should be avoided and the importance of healthy nutrition should be emphasized.